2005
DOI: 10.1111/j.1365-2141.2005.05764.x
|View full text |Cite
|
Sign up to set email alerts
|

JAK2V617F mutation in essential thrombocythaemia: clinical associations and long‐term prognostic relevance

Abstract: Jelinek et al, 2005;Jones et al, 2005;Kralovics et al, 2005;Levine et al, 2005;Steensma et al, 2005;Zhao et al, 2005). JAK2 V617F represents a somatic point mutation involving exon 12 of the JAK2 gene that results in the substitution of valine by phenylalanine at codon 617. The highest mutational frequency was reported in PV (65-97%) but the mutation also occurs in a spectrum of both typical and atypical MPD including ET (23-57%), MMM (35-50%), systemic mastocytosis (0-25%), chronic neutrophilic leukaemia (17-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
245
3
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 289 publications
(286 citation statements)
references
References 31 publications
34
245
3
4
Order By: Relevance
“…The role of JAK2 V617F , mutation as independent factor for thrombosis is still debated [7,[16][17][18][19][20]. In our series, we did not find any significant role of JAK2 V617F for predicting thrombosis, but some limit of our analysis should be considered because we cannot exclude that this may reflect an inadequate sample size.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The role of JAK2 V617F , mutation as independent factor for thrombosis is still debated [7,[16][17][18][19][20]. In our series, we did not find any significant role of JAK2 V617F for predicting thrombosis, but some limit of our analysis should be considered because we cannot exclude that this may reflect an inadequate sample size.…”
Section: Discussionmentioning
confidence: 56%
“…In the last few years, new information on the pathogenesis of thrombosis in MPNs became available, including the role of leukocyte activation and interaction with platelets as well as the presence of JAK2 V617F mutation [5,6]. Very recently, leukocytosis has been reported as an independent risk factor for thrombosis in both PV and ET [7][8][9][10] and this is particularly true in "low-risk" patients who normally do not require cytoreductive therapy. However, additional data are required to firmly establish the role of such predictors for thrombosis as well as their clinical advantage.…”
Section: Introductionmentioning
confidence: 99%
“…negative for all three mutations) [4,42]. It is also important to note that other JAK2/CALR/MPL mutated MPN (or myelodysplastic syndromes [MDS]/MPN) can mimic ET in their presentation; these include prefibrotic PMF [4,43] and refractory anemia with ring sideroblasts with marked thrombocytosis (RARS-T) [4,44].…”
Section: Diagnosismentioning
confidence: 99%
“…Subsequent studies confirmed the presence of JAK2V617F in almost all patients with PV [28,29] and in 50-60% of those with ET [30][31][32][33] or PMF [34,35]. In 2006, a somatic MPLW515L exon 10 mutation (a G to T transition at nucleotide 1544 resulting in a tryptophan to leucine substitution at codon 515 of the transmembrane region) was described in JAK2V617F-negative PMF [24].…”
mentioning
confidence: 87%